2009
DOI: 10.1590/s1413-86702009000100012
|View full text |Cite
|
Sign up to set email alerts
|

A study of iga antibody response to different mycobacterium tuberculosis antigens in the diagnosis and monitoring of pulmonary tuberculosis

Abstract: We evaluated the performance of the ELISA technique in the detection of IgA antibodies against different Mycobacterium tuberculosis antigenic preparations in serum samples from 49 patients with pulmonary tuberculosis collected before and after the start of specific treatment. The controls consisted of serum samples from healthy patients without any prior contact with the bacteria and serum samples from patients with other pneumopathies. Glycolipid antigen gave the best diagnostic performance, with a sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 23 publications
(23 reference statements)
2
14
1
6
Order By: Relevance
“…IgA is the most abundantly produced mammalian immunoglobulin, and although IgA-secreting plasma cells are concentrated along mucous membrane surfaces, it is produced in the pleural space, since the pleura is a serous membrane (28,41). On the other hand, several authors have pointed to the presence of IgA against the mycobacterial antigens in the serum of TB patients (3,11,33,45). Regrettably, in our study, serum samples of patients were not available for a matching analysis.…”
Section: Discussionmentioning
confidence: 78%
“…IgA is the most abundantly produced mammalian immunoglobulin, and although IgA-secreting plasma cells are concentrated along mucous membrane surfaces, it is produced in the pleural space, since the pleura is a serous membrane (28,41). On the other hand, several authors have pointed to the presence of IgA against the mycobacterial antigens in the serum of TB patients (3,11,33,45). Regrettably, in our study, serum samples of patients were not available for a matching analysis.…”
Section: Discussionmentioning
confidence: 78%
“…This could be an additional evidence for the potential of IgA antibody in the development of serological diagnostic tools for latent TB [40,44], which warrants further studies like in household contacts of patients with smear-positive PTB.…”
Section: Discussionmentioning
confidence: 79%
“…Conde et al [38] suggested that IgA antibody against P-90 antigen can distinguish individuals recently infected with Mtb. Arikan et al [39] and Bezerra et al [40] have evaluated the performance of ELISA-based IgA antibody for the diagnosis of active TB using different Mtb antigens and suggested that serum IgA antibody has a promising role in the diagnosis of active TB. Skvor et al [41] have reported an increased level of IgA in relation to the extent of disease in patients with PTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have described the presence of IgA against the mycobacterial antigens in the serum of TB patients [26,28-31], suggesting that this immunoglobulin isotype is present in both patients with newly acquired infections and those of a longer duration [32]. In the present investigation, the positive rate of IgA was not too high in active TB patients at their first visit to the outpatient clinic and the IgA antibody levels were maintained for a longer duration until the completion of anti-TB chemotherapy.…”
Section: Discussionmentioning
confidence: 99%